2009
DOI: 10.1073/pnas.0901387106
|View full text |Cite
|
Sign up to set email alerts
|

The bouquet of grapevine (Vitis viniferaL. cv. Cabernet Sauvignon) flowers arises from the biosynthesis of sesquiterpene volatiles in pollen grains

Abstract: Terpenoid volatiles are important information molecules that enable pollinators to locate flowers and may protect reproductive tissues against pathogens or herbivores. Inflorescences of grapevine (Vitis vinifera L.) are composed of tiny green flowers that produce an abundance of sesquiterpenoid volatiles. We demonstrate that male flower parts of grapevines are responsible for sesquiterpenoid floral scent formation. We describe temporal and spatial patterns of biosynthesis and release of floral volatiles throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…The specific expression profile of TPS03 in the stigma and sepal of Col-0 flowers may reflect the functions of (E,E)-a-farnesene in pollinator attraction or florivore/ antimicrobial defense, as discussed for the flowerspecific genes TPS21 [encoding a (E)-b-caryophyllene synthase; Tholl et al, 2005] and TPS24 (a multiproduct monoterpene synthase), which exhibit similar expression patterns in Arabidopsis flowers (Chen et al, 2003b). Interestingly, TPS03 promoter activity was observed in pollen grains and resembles the recently reported expression of a valencene sesquiterpene synthase in the pollen of grape (Vitis vinifera) flowers (Martin et al, 2009). A pattern of constitutive expression in reproductive organs and induced expression in vegetative tissues has also been observed for Arabidopsis geranyllinalool synthase (TPS04/GES; Herde et al, 2008) in the formation of the volatile homoterpene TMTT and has been demonstrated for other genes involved in plant defense (Pollak et al, 1993;Hoegen et al, 2002;Stotz et al, 2009).…”
Section: Tps02 and Tps03 Expression Is Under Constitutive Control In mentioning
confidence: 71%
“…The specific expression profile of TPS03 in the stigma and sepal of Col-0 flowers may reflect the functions of (E,E)-a-farnesene in pollinator attraction or florivore/ antimicrobial defense, as discussed for the flowerspecific genes TPS21 [encoding a (E)-b-caryophyllene synthase; Tholl et al, 2005] and TPS24 (a multiproduct monoterpene synthase), which exhibit similar expression patterns in Arabidopsis flowers (Chen et al, 2003b). Interestingly, TPS03 promoter activity was observed in pollen grains and resembles the recently reported expression of a valencene sesquiterpene synthase in the pollen of grape (Vitis vinifera) flowers (Martin et al, 2009). A pattern of constitutive expression in reproductive organs and induced expression in vegetative tissues has also been observed for Arabidopsis geranyllinalool synthase (TPS04/GES; Herde et al, 2008) in the formation of the volatile homoterpene TMTT and has been demonstrated for other genes involved in plant defense (Pollak et al, 1993;Hoegen et al, 2002;Stotz et al, 2009).…”
Section: Tps02 and Tps03 Expression Is Under Constitutive Control In mentioning
confidence: 71%
“…2), are likely to have different ecological roles. For example, as proposed for floral terpenes in Arabidopsis (Chen et al, 2003), an important role for the non-petalassociated floral terpenes in apple and other plants, including grapevine (Martin et al, 2009) and Magnolia spp. (Lee and Chappell, 2008), could be to provide protection for the reproductive organs, and more specifically, the germ line cells, against oxidative stress and pathogenic microbes.…”
Section: Discussion Volatile Terpene Production In CV Royal Gala Appementioning
confidence: 99%
“…Of enzymes related to terpene synthesis, GLL synthase was strongly up-regulated. GLL comprises up to 95% of terpenes found in other sink tissues, such as flowers and berries (36).…”
mentioning
confidence: 99%